Chia (Salvia hispanica) Gene Expression Atlas Elucidates Dynamic Spatio-Temporal Changes Associated With Plant Growth and Development - Gupta, Parul; Geniza, Matthew; Naithani, Sushma; Phillips, Jeremy L.; Haq, Ebaad; Jaiswal, Pankaj (Frontiers in Plant Science, 2021)
Chia (Salvia hispanica L.), now a popular superfood and a pseudocereal, is one of the richest sources of dietary nutrients such as protein, fiber, and polyunsaturated fatty acids. At present, the genomic and genetic information available in the public domain for this crop is scanty, which hinders understanding its growth and development as well as genetic improvement. We report RNA-Seq based comprehensive transcriptome atlas of Chia sampled from 13 tissue types covering vegetative and reproductive growth stages. We used ~355 million high-quality reads out of total ~394 million raw reads from transcriptome sequencing to generate de novo reference transcriptome assembly and the tissue-specific transcript assemblies. After quality assessment of merged assemblies and implementing redundancy reduction methods, 82,663 reference transcripts were identified. 65,587 out of 82,663 transcripts were translated into 99,307 peptides, and we were successful in assigning InterPro annotations to the 45,209 peptides and Gene Ontology terms to 32,638 peptides. The assembled transcriptome is estimated to have complete sequence information for ~86% of the genes found in the Chia genome. Furthermore, the analysis of 53,200 differentially expressed transcripts revealed their distinct expression patterns in Chia's vegetative and reproductive tissues; tissue- and developmental stage-specific networks of transcription factors; and regulation of expression of enzyme coding genes associated with important metabolic pathways. In addition, we identified 2,411 simple sequence repeat (SSRs) as potential genetic markers from the transcripts. Overall, this study provides a comprehensive transcriptome atlas, and SSRs, contributing to building essential genomic resources to support basic research, genome annotation, functional genomics, and molecular breeding of Chia. An earlier version of this manuscript was submitted to preprint archive bioRxiv https://www.biorxiv.org/content/10.1101/2020.10.09.333419v1